Passive Hand Movements Disrupt Adults’ Counting Strategies - Imbo, Ineke; Vandierendonck, André; Fias, Wim (Frontiers in Psychology, 2011)
In the present study, we experimentally tested the role of hand motor circuits in simple-arithmetic strategies. Educated adults solved simple additions (e.g., 8+3) or simple subtractions (e.g., 11–3) while they were required to retrieve the answer from long-term memory (e.g., knowing that 8+3 = 11), to transform the problem by making an intermediate step (e.g., 8+3 = 8+2+1 = 10+1 = 11) or to count one-by-one (e.g., 8+3 = 8…9…10…11). During the process of solving the arithmetic problems, the experimenter did or did not move the participants’ hand on a 4-point matrix. The results show that passive hand movements disrupted the counting strategy while leaving the other strategies unaffected. This pattern of results is in agreement with a procedural account, showing that the involvement of hand motor circuits in adults’ mathematical abilities is reminiscent of finger counting during childhood.